A Local Government Application Capability Level Information System Audit using COBIT 5 Framework - Bagus Dwi Andika; Sucipto Sucipto; Arie Nugroho (Politeknik Negeri Cilacap, 2023)
The ASN application stores State Civil Apparatus and Employee Work Target master data. ASN application has never been audited. This study aimed to measure the capability level of the ASN application using the COBIT 5 framework. The audit results contain current findings and expectations for the future, then analyze the gaps and make recommendations for improvement. Audit results based on domains DSS01, DSS02, DSS03, DSS04, DSS05, and DSS06 achieve capability level 1 performance process. The ASN application manager has successfully implemented a process that has achieved its goals by finding evidence of work product output. To achieve the expected level, namely level 2 managed process, it is recommended that you complete incomplete output documents and carry out activities that have not been carried out per COBIT 5.